Assessing the quality of educational short videos on dry eye care: a cross-sectional study - Huang, Mingxue; Wang, Jiaoman; Wei, Jiawen; Zhang, Rongkui; Wang, Xiaoyan; Gan, Jinhua; Zhang, Zhe; Liu, Fangyan (Frontiers in Public Health, 2025)
BackgroundShort video social media platforms play a crucial role in public health by effectively disseminating health information. Despite this, many educational videos on dry eye care have not received sufficient attention. This study aimed to conduct a comprehensive analysis and evaluate the quality of educational short videos on dry eye care available on TikTok.MethodsOn August 30, 2024, the top 200 videos related to dry eye were viewed from the Chinese version of TikTok using the platform’s default ranking. The overall quality, reliability, comprehensibility, and applicability of the videos are systematically evaluated using the DISCERN and PEMAT-A/V assessment tools.ResultsA total of 199 videos were included in the study and categorized based on account information: medical professional individual users, general professional individual users, for-profit organizations, non-profit organizations, and news organizations. Medical professionals were the predominant uploaders, contributing 81% of the videos. The overall misinformation rate was 2%. A majority of the videos (85.9%) addressed at least two aspects of dry eye, while only 14.1% covered three or more topics. The videos scored 22.4 ± 6.4 for reliability and 17.4 ± 6.2 for treatment options. Upon evaluation, the understandability and actionability of these videos were found to be 79.1% and 60.4%, respectively.ConclusionTikTok holds significant potential for disseminating health information, primarily through content created by medical professionals. Currently, much of the content focuses on the symptoms and management of dry eye, with limited discussion on its definition, classification, and diagnosis. While most video content is reliable, there is a risk of incomplete or inaccurate information, these videos can serve as a reference. Therefore, the public should exercise caution when seeking information on dry eye through TikTok and individuals experiencing symptoms are advised to consult healthcare professionals for accurate diagnosis and treatment.